2017
DOI: 10.1186/s13002-017-0183-6
|View full text |Cite
|
Sign up to set email alerts
|

Use of cultivated plants and non-plant remedies for human and animal home-medication in Liubań district, Belarus

Abstract: BackgroundTo use any domestic remedy, specific knowledge and skills are required. Simple logic dictates that the use of wild plants in the context of limited interaction with nature requires prior identification, while in the case of non-plant remedies and cultivated plants this step can be omitted. This paper aims to document the current and past uses of non-plant remedies and cultivated plants in the study region for human/animal medication; to analyze the human medicinal and veterinary use areas in the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…Twenty-four taxa were named by one person and 12 by two people. More than half of the taxa (45) were collected from the wild. Some wild taxa were also cultivated for medicinal use (e.g., Origanum vulgare) or for food, and then used for medicine (e.g., Ribes nigrum, Rubus idaeus), or purchased (e.g., Valeriana officinalis).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-four taxa were named by one person and 12 by two people. More than half of the taxa (45) were collected from the wild. Some wild taxa were also cultivated for medicinal use (e.g., Origanum vulgare) or for food, and then used for medicine (e.g., Ribes nigrum, Rubus idaeus), or purchased (e.g., Valeriana officinalis).…”
Section: Resultsmentioning
confidence: 99%
“…Animal breeding involves maintaining animal health and welfare. Scholars have found that the knowledge related to healing and ensuring the welfare of domestic animals has been largely abandoned in industrialized areas of Europe (3), while it appears to be relatively alive in rural contexts of the Mediterranean (4) and in some areas of Eastern Europe, e.g., Belarus (5)(6)(7). In the Mediterranean region, folk veterinary knowledge has been partially preserved due to geographical isolation and distance from veterinary services, yet it is rapidly declining and being replaced by modern livestock farming technologies and administrative veterinary controls (4).…”
Section: Introductionmentioning
confidence: 99%
“…Among possible pan-Soviet elements, Aesculus hippocastanus infused in alcohol for relieving joint and rheumatic pain was also reported in Belarus Sõukand et al (2017a) and in Estonia (Sõukand and Kalle 2011), where an increase in use was also detected during Soviet times. Another plant common to other Eastern European countries is Aloe spp., which is used especially for treating the skin but also the digestive system ( Sõukand et al, 2017b ). Linum usitatissimum , well known in Estonia for its ethnoveterinary for its ethnoveterinary properties ( Kalle and Kaas, 2020 ), is still sometimes used for the digestive system ( Sõukand et al, 2017b ).…”
Section: Discussionmentioning
confidence: 99%
“…Another plant common to other Eastern European countries is Aloe spp., which is used especially for treating the skin but also the digestive system ( Sõukand et al, 2017b ). Linum usitatissimum , well known in Estonia for its ethnoveterinary for its ethnoveterinary properties ( Kalle and Kaas, 2020 ), is still sometimes used for the digestive system ( Sõukand et al, 2017b ). Finally, Ribes nigrum was mentioned on the Romanian side of the border but only for food purposes, and in Ukraine, it was also mentioned for treating the circulatory and cardiovascular systems, and it was reported for several other uses in Belarus ( Sõukand et al, 2017b ).…”
Section: Discussionmentioning
confidence: 99%